Effect Of Planting And Old Media Volume Zpt Immersion Against Early Growth Of Cane Seeds (Saccharum Officinarum L) Chip Bud System - Andriani Eko Prihatiningrum; Moch R Syarifuddin Fathony (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to determine the effect of the interaction between the treatment of the effect of the volume of the planting medium and the duration of immersion of zpt on growth the beginning of sugarcane seedlings (Saccharum officinarum L) bud chip system, carried out at the green hause of Muhammadiyah University of Sidoarjo from November to January 2016. The research used a factorial randomized block design (RAK), consisting of two factors and three replications. The first factor was the treatment for the duration of ZPT immersion which consisted of 4 levels, namely without ZPT immersion, 2 hours of ZPT immersion, 4 hours of ZPT immersion, 6 hours of ZPT immersion, 8 hours of ZPT immersion, while the second factor was the volume of the planting medium which consisted of two types, i.e. 80ml, 200ml. Based on the results of the study, the analysis of various combinations of treatment combinations of planting media volume and immersion time of ZPT had no significant effect on the variables of plant height, number of leaves, plant diameter, root length, root weight. ZPT immersion in bud chip system sugarcane seedlings at time intervals did not show a significant effect. The use of volume of planting media at the level of 80 ml and V2 200 ml showed a very real interaction. The best use of the volume of planting media with 200 ml per sugarcane bud chip seed.